Regulation of choice behavior : an experiment investigating the hypothesis that people bundle sequences of expected rewards - Schuhr, Alexander (School of Economics, 2015)
This thesis discusses reward bundling as a process that enables decision makers to self-regulate their choice behavior. Most empirical work on intertemporal choice has focused on analyzing impulsive choice. Less effort has been dedicated to explanations of how individuals manage to overcome self-defeating behavior. This thesis evaluates the theory of reward bundling. It presents a set of econometric tools that can be employed to investigate whether actual choice behavior is consistent with the theory of bundling. It reports an experiment with human subjects. Reward bundling has been demonstrated in experiments with pigeons and rats. However, no empirical study using salient rewards and sound econometric model estimation has ever been carried out with humans. The present experiment is, therefore, the first that meets the methodological standards of experimental economics and finds evidence consistent with the presence of reward bundling.